2009
DOI: 10.1002/jcp.21744
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Golgi pH impairs terminal N‐glycosylation by inducing mislocalization of Golgi glycosyltransferases

Abstract: Acidic pH of the Golgi lumen is known to be crucial for correct glycosylation, transport and sorting of proteins and lipids during their transit through the organelle. To better understand why Golgi acidity is important for these processes, we have examined here the most pH sensitive events in N-glycosylation by sequentially raising Golgi luminal pH with chloroquine (CQ), a weak base. We show that only a 0.2 pH unit increase (20 microM CQ) is sufficient to markedly impair terminal alpha(2,3)-sialylation of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 61 publications
8
108
0
1
Order By: Relevance
“…A study showed that the pH of the medium had an impact on the distribution of the glycoforms of a murine hybridoma secreted IgG (Rothman et al, 1989). Mislocalization of certain Golgi glycosyltransferases has been suggested to be the primary reason for the pHinduced glycosylation defects (Rivinoja et al, 2009). …”
Section: Phmentioning
confidence: 99%
“…A study showed that the pH of the medium had an impact on the distribution of the glycoforms of a murine hybridoma secreted IgG (Rothman et al, 1989). Mislocalization of certain Golgi glycosyltransferases has been suggested to be the primary reason for the pHinduced glycosylation defects (Rivinoja et al, 2009). …”
Section: Phmentioning
confidence: 99%
“…pH Sensitivity of Enzyme Complexes-Previously, we have reported that a slight drug-induced increase in Golgi pH results in mislocalization of ST3Gal-III (but not of ST6Gal-I) into the endosomal compartments, probably reflecting differences in complex formation (35). Therefore, we tested the pH sensitivities of the enzyme homo-and heteromers in live cells by using FRET.…”
Section: Volume 286 • Number 44 • November 4 2011mentioning
confidence: 99%
“…For example, Acidic pH of the Golgi lumen is known to be crucial for correct glycosylation, and even minor changes in the PH can impair N-glycosylation. 11 Further support comes from diseases. Since as we suggest glycosylation is highly sensitive to the biochemical environment and glycoprotein patterns reflect the internal and external environment of the cells in which proteins are glycosylated they can be sensitive indicators of alternation in cell function brought about by disease or stress.…”
Section: Immune Recognition Is Often Based On Recognition Of Carbohydmentioning
confidence: 99%